Pengaruh Metode Pembelajaran dan Minat Belajar Terhadap Hasil Belajar IPA - Effiyati Prihatini (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2017)
The purpose of this study to determine the effect of learning methods on the mastery of the concept of science. To know the influence of student's learning interest to mastery of science concept. To know the influence of interactive learning method and student's interest in the mastery of science concept. The research method used was a Quasi-experimental method with the Quantitative approach. The research was conducted in Mts Negeri 1 South Jakarta and Mts N 23 South Jakarta in the academic year 2016/2017. The sample in this study amounted to 70 students with random sampling. Hypothesis testing with 2 way ANOVA. The result of the research shows that there is a significant influence on the use of learning media to the learning outcomes of science, there is a significant influence of learning interest on the learning outcomes of science, there is a non-significant influence of the interaction of learning methods and the interest of learning on the science learning outcomes.